La raza y la definición de la identidad del “Indio” en las fronteras de la América española Colonial - Robert H. Jackson (Revista de Estudios Sociales, 2007)
The following study examines the process of the creation of indio identity and status, at least on paper, that defined the role of the natives in colonial society, on three distinct mission frontiers on the fringes of Spanish America. The mission was a frontier institution designed to acculturate and ostensibly transform native populations into sedentary agriculturalists, and incorporate natives into the new colonial order. The first is the Jesuit Chiquitos mission frontier of eastern Upper Peru (modern Bolivia), populated by ethnically diverse sedentary agriculturalists. The second is the Jesuit mission frontier of Paraguay with more a homogeneous Guaraní population. The final case study comes from the Franciscan missions of northern Coahuila (Mexico) populated by small bands of nomadic hunter-gatherers.